DESKRIPSI COMMOGNITIVE SISWA KELAS VIII DALAM MEMAHAMI MATERI LINGKARAN BERDASARKAN GAYA BELAJAR DI SMP - Nurul Warda; Andi Alim Syahri; Ernawati (STKIP Subang, 2024)
This research aims to describe students' cognitive skills in solving circle problems in terms of learning style. This type of research is descriptive qualitative. The research subjects were class VIII students at SMPN 51 Makassar. There were 3 research subjects with one student each from the visual learning style, one student from the auditory learning style, and one student from the kinesthetic learning style. Research data was taken from learning style questionnaires, student written tests, and interviews. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The learning style questionnaire is used to determine students' learning style tendencies, while the written test is to determine students' cognitive abilities. The research results show that students' cognitive abilities in solving problems in each learning style are different. Students with a visual learning style solve problems using the four cognitive components, namely word use, visual mediators, narratives, and routines. Students with an auditory learning style solve problems using two cognitive components, namely narrative and routine. Meanwhile, students with a kinesthetic learning style use the four cognitive components, namely word use, visual mediators, narratives, and routines.